Penegakan Hukum Luar Biasa Atas Kejahatan Ekosida Sebagai Extraordinary Crime Dalam Konsep Hukum Lingkungan Internasional - Siti Khairunnissa; Fajar Khaify Rizky; Siti Nurahmi Nasution; Boy Laksamana (Riau Law Journal, 2022)
The purpose of this research is to analyze law enforcement against the crime of ecocide as extraordinary crime. Second, law enforcement review against ecocides in various regulations and various court decisions in Indonesia Third, to analyze the concept of international environmental law in the extraordinary enforcement law against ecocide crimes (Extraordinary Crime) The research method used by researchers is normative juridical approach. This means that the legal material used as a study is secondary data.